Localized surface states influence in the photoelectrocatalytic performance of Al doped a-SiC:H based photocathodes - del Carmen Mejia, M.D.C.; Kurniawan, M.; Knauer, A.; Rumiche, F.; Bund, A.; Guerra Torres, J.A. (Elsevier, 2022)
In this work we evaluate the role of a-SiC:H(p)/SiO2 localized surface states (SS) in the Photoelectrochemical Water Splitting reaction. The analysis was carried out in three steps. First, retrieving the a-SiC:H(p) SS, energy distribution and density, by Electrochemical Impedance Spectroscopy techniques. Second, relating these results with direct measurements over the a-SiC:H(p)/SiO2 surface using X-ray Photoelectron spectroscopy. Finally, assessing the SS influence in the photo-induced hydrogen reduction by testing the a-SiC:H(p) photocathode with Linear Sweep Voltammetry. The whole analysis was done after subjecting the a-SiC:H(p) surface to different annealing treatments, i.e. 600 °C and 700 °C, necessary to obtain the required ohmic contacts. We believe that the participation of SS in an indirect electron charge transfer to the electrolyte, is kinetically feasible to take place in an a-SiC:H surface with relatively low SS density, 0.3x1012 cm-2. Whilst higher SS densities, in the range of 1.48 x 1014 cm-2, would trigger undesired charge carrier recombination.
Keywords: Photoelectrochemical; https://purl.org/pe-repo/ocde/ford#1.04.05